International Development And Health: The Case Of A Development NGO In The Fight Against The Covid-19 Pandemic In Andhra Pradesh, India - Pincay, Cristhian Marcelo Gorozabel; Diaz, Rylan Wenzell; Leblond, Antonin (Seven Editora, 2023)
The international cooperation for development system traces its origins from the end of World War II. Currently, it does not revolve exclusively around developed states as principal actors. On the contrary, it possesses a pluralistic and decentralized characteristic, different of what used to dominate between the 50s and the 60s. In this context, this article aims to recognize and highlight the role played by non-governmental development organizations in international cooperation. It was developed from a qualitative approach using bibliographic-documentary review procedures. The case study method was utilized as its research method, basing on the experience of an organization that operates in two impoverished areas of southern India, the Vicente Ferrer Foundation. DOI: https://doi.org/10.56238/colleinternhealthscienv1-125